2012
DOI: 10.1042/cbi20110618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in vitro cultured bone marrow and adipose tissue‐derived mesenchymal stem cells and their ability to express neurotrophic factors

Abstract: MSCs (mesenchymal stem cells) have attracted attention as a promising tool for regenerative medicine and transplantation therapy. MSCs exert neuroprotective effects by secreting a number of factors in vitro and in vivo. Similar characteristics are found in ADSCs (adipose-derived stem cells) and BMSCs (bone marrow stromal cells). Multipotent capability, easy accessibility and rapid proliferation of ADSCs have been established. Our main objective was to compare cell viability, growth rate, expression of neurotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 46 publications
7
25
0
3
Order By: Relevance
“…Interestingly, differences in proliferation rate were seen among MSCs obtained from diverse tissues [88]. In order to reach sufficient amount of cells at early passages, new strategies have recently been applied.…”
Section: Strategies To Increase Mscs Migratory Survival and Prolifermentioning
confidence: 99%
“…Interestingly, differences in proliferation rate were seen among MSCs obtained from diverse tissues [88]. In order to reach sufficient amount of cells at early passages, new strategies have recently been applied.…”
Section: Strategies To Increase Mscs Migratory Survival and Prolifermentioning
confidence: 99%
“…Yet, its effect on microglia proliferation is still controversial. Tambuyzer et al found that the proliferation of microglial significantly increased compared with control cells when a lower concentration (10 fM) recombinant OPN was added to the culture medium, which indicated that OPN also stimulated proliferation of microglia [18]. However, Rabenstein et al put forward the opposite conclusion.…”
Section: The Effect Of Opn On Microgliamentioning
confidence: 99%
“…Treating these cells with OPN for 24 hours significantly increased the phagocytotic activity compared with microglia cultured in control medium. The uptake of beads by microglia treated with 1 nM OPN was almost doubled that of control cells, thereby largely restoring the activity to the level observed immediately after harvesting [18]. Therefore, they believe that OPN can increase the phagocytic activity of microglia.…”
Section: The Effect Of Opn On Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, mesenchymal stem cells (MSCs) from adipose tissue can be harvested less invasively and with greater ease compared to other tissues listed above. In addition, these cells have a higher selfrenewal capacity and proliferative ability [8e10], and produce an abundance of humoral factors [11,12]. By transplanting adipose tissue-derived multi-lineage progenitor cells (ADMPCs) into canine experimental periodontal disease models, we have demonstrated that ADMPC induces significant periodontal tissue regeneration [13].…”
Section: Introductionmentioning
confidence: 99%